EDUCATIONAL DIALOGUE AS A PREREQUISITE READYNESS OF FUTURE TEACHERS TO DIALOGUE TEACHING OF SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2007)
Dialogical approach in the professional training of teachers provides leading role of instructor and subordinate position of student into equal interaction. Training dialogue using in educational process of higher pedagogical educational establishment is a prerequisite of dialogical training of schoolchildren.